2018
DOI: 10.1002/marc.201800404
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Self‐Assembly and Dynamic Exchange of Supramolecular Nanocages Based on Terpridine Building Blocks

Abstract: Coordination-driven self-assembly as a powerful bottom-up approach has been extensively used to construct multifarious supramolecular architectures with increasing complexity and functionality. Due to the unique cavity structures and precisely controllable dimensions, 3D supramolecules display unprecedented properties and functions in catalysis, sensing, gas storage, and smart materials. Herein, we have built two 3D nanocages with different sizes by changing the length of the organic ligand arms. The structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Similar to the iodonium ion, the presence of (transition)metal cation can induce self‐assembly of organic ligands leading to the formation of structurally rich family of metallosupramolecular complexes. Numerous examples show the complementarity of the gas‐phase structures of metallosupramolecular systems, obtained by IM‐MS, with those observed in solution or even in the solid state revealed by NMR or X‐ray crystallography, respectively (Jiang et al, 2019; Lloyd Williams & Rijs, 2021; Sarkar et al, 2020; Wang, Liu, et al, 2018; Wang, Zhang, et al, 2018; Zhang, Wang, et al, 2018).…”
Section: Im‐ms Analysis—insight Into the Solution Or The Gas Phase St...mentioning
confidence: 99%
“…Similar to the iodonium ion, the presence of (transition)metal cation can induce self‐assembly of organic ligands leading to the formation of structurally rich family of metallosupramolecular complexes. Numerous examples show the complementarity of the gas‐phase structures of metallosupramolecular systems, obtained by IM‐MS, with those observed in solution or even in the solid state revealed by NMR or X‐ray crystallography, respectively (Jiang et al, 2019; Lloyd Williams & Rijs, 2021; Sarkar et al, 2020; Wang, Liu, et al, 2018; Wang, Zhang, et al, 2018; Zhang, Wang, et al, 2018).…”
Section: Im‐ms Analysis—insight Into the Solution Or The Gas Phase St...mentioning
confidence: 99%
“…The complementarity of IMS-MS when added as a characterisation technique cannot be overstated, with numerous recent examples of structural agreement between IMS-MS, x-ray crystallography and NMR/DOSY NMR, TEM etc. ( Chan et al, 2009 ; Brocker et al, 2010 ; Chan et al, 2011 ; Lu et al, 2014 ; Wang et al, 2014a ; Wang et al, 2014c ; Bonakdarzadeh et al, 2015 ; Liang et al, 2015 ; Xie et al, 2015 ; Li et al, 2016 ; Xie et al, 2016 ; Wang et al, 2018a ; Wang et al, 2018b ; Zhang et al, 2018 ; Jiang et al, 2019 ; Sarkar et al, 2020 ) Indeed, recent examples have shown, adding IMS-MS to the characterisation workflow can help avoid missing products due to, for example, a lack of crystallization ( Christie et al, 2016 ).…”
Section: Applications Of Ion Mobility Mass Spectrometry To Study Coordination Driven Self-assemblymentioning
confidence: 99%
“…Following this thought, two metallo‐organic tpy ligands L26 and L27 with different lengths were subsequently synthesized and two 3D nanocages ( S38 and S39 ) with the same structures were obtained by self‐assembling these two ligands with Zn(II), respectively ( Figure a). [ 97 ] Moreover, the dynamic ligand exchange behavior between these two nanocages was investigated by means of ESI‐MS and TWIM‐MS. The results underscored the versatility of these 3D supramolecular architectures in that they proved capable of tolerating different sizes of ligands with various combinations and forming hybrid self‐assembled nanocages.…”
Section: D Metallosupramolecular Architectures Based On Stepwise Self...mentioning
confidence: 99%